Looking Back and Looking Forward : Can Organized Labour Stand the Test of Time? - Crispo, John H. G. (Relations industrielles / Industrial Relations, 1965)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

International Unionism: A Study in Canadian-American Relations - Crispo, John H. G. (McGraw-Hill of Canada, 1967)
The relationship between the Canadian and American labour movements is unique. It has given rise to considerable controversy and yet has been the subject of surprisingly little intensive examination. While a fair amount has been written about this unusual phenomenon, little of this material is very complete or incisive. As a result the door has been left open for those with an axe to grind to express themselves freely on the subject without the fear of contradiction based on cold hard facts. This study may reduce the frequence of such utterances in the future. It endeavours to deal objectively with an area of Canadian-American relations where emotions and prejudices have distorted public debate. Many of the events which have provided fuel for this debate over the past few years are dealt with, including the Seafarers' International Union dispute on the Great Lakes and the Internaitonal Typographical Union strike againist the three Toronto newspapers. –Preface. Contents: Introduction (pages 1-10) – Explaining the presence of international unionism in Canada (pages 11-49) – The Canadian membership within international unions (pages 50-95) – Relations between the central federations of labour in Canada and the United States (pages 96-145 – The unity and structure of the Canadian labour movement /(pages 146-178) – Collective bargaining policies and practices in Canada (pages 179-230) – Policies and practices outside the area of collective bargaining (pages 231-258) – The flow of funds and benefits across the border (pages 259-278) – Employer and government attitudes towards international unionism (pages 279-301) – Summary and conclusion (pages 302-324) – A selected bibliography (pages 325-327).
OCLC: 232617

The Role of International Unionism in Canada - Crispo, John H. G. (Canadian-American Committee, 1967)
The relationship between the Canadian and American labour movements is unique. It has given rise to considerable controversy and yet has been the subject of surprisingly little intensive research. As a result those with an axe to grind have been able to express themselves without fear of contradiction based on cold, hard facts. This study may reduce the frequency of such utterances. It endeavors to deal objectively with an area of Canadian-American relations where emotion and prejudice have distorted public debate. The reader will have to judge for himself whether sufficient detachment has been shown to achieve real objectivity. –From author's preface
Keywords: Labor unions – Canada

Industrial Relations: Challenges and Responses - Crispo, John H. G. (University of Toronto Press, 1966)
Industrial relations, which in the past have focused almost entirely on union-management relations, have recently been expanded to include such new areas of interest as manpower and poverty problems. At the University of Toronto a new Centre for Industrial Relations has been established, a research-oriented institution whose primary objective is to further scholarly investigations into all phases of industrial relations. To launch the new Centre a conference was held with distinguished Canadian and international authorities invited to discuss the challenges and responses for Industrial Relations in the next decade, from various points of view. This volume, based on the papers presented, will be a welcome contribution to knowledge in this challenging field. In Part I, "An International Perspective," David A. Morse considers the conference's general theme in terms of its world-wide ramifications. Part II, "Collective Bargaining in an Age of Change," is devoted mainly to a discussion of the impact of industrial change on collective-bargaining institutions and practices. James R. Bright begins with a reminder that there are two schools of thought about the effect of automation upon such variables as skill and wage differentials. Then Frederick Harbison and Arnold R. Weber assess the recent record of collective bargaining: Professor Harbison provides a wide-ranging analysis of the performance of the American collective-bargaining system to date, and Professor Weber describes the effect of technological change upon the respective power of union and management, upon negotiating procedures, and upon the substantive results of collective bargaining. Harry W. Arthurs explores the role of law in coping with change, especially the technological variety. The third part of the volume, "On the Frontier of Industrial Relations," considers two of the many new industrial relations problems: Wilbert E. Moore, discussing the individual in an organizational society, asks for a reconsideration of the roles of institutional responses to the challenges posed by industrialization. Finally, there are two discussions devoted to one of the most pressing economic and social problems: poverty. The Honourable Maurice Sauvé, who, as Canada's Minister of Forestry, is in charge of the Agriculture Rehabilitation and Development Act, discusses the earnest response of governments to the challenge of poverty; Tom Cosgrove, discussing the United States "war on poverty," reviews the dimensions of the challenge posed by poverty in the United States and outlines the federal legislative response to date. These provocative contributions should be received with great interest by representatives of labour, management, and government, as well as by those members of the public who are concerned with the problems of a growing industrial society. –Publisher's description
Book available at Internet Archive to people with print disabilities: http://archive.org/details/industrialrelati0000cris
Keywords: Collective bargaining